2023
DOI: 10.29303/jppipa.v9i1.2511
|View full text |Cite
|
Sign up to set email alerts
|

QR Code-Practicum Guide Based on Guided Inquiry as The Novel Biology Lab Activities Learning Assisted

Abstract: Educators play an important role in developing learning tools that are interesting and by the needs of students. This aims to develop a QR Code-Practical Guide based on Guided Inquiry for Class XII MIPA at the High School Level on growth and development in plants and photosynthesis and to determine the validity, practicality, and effectiveness. This type of research is Research and Development with the ADDIE model which consists of 5 stages, namely Analyze, design, development, Implementation, and evaluation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…They have been shown to enhance student interest in learning, foster teamwork skills, and broaden cultural perspectives, thereby promoting the development of global competencies [12]. QR codes have been widely implemented in educational institutions, including universities and colleges, to enhance the effectiveness of teaching and learning processes [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been shown to enhance student interest in learning, foster teamwork skills, and broaden cultural perspectives, thereby promoting the development of global competencies [12]. QR codes have been widely implemented in educational institutions, including universities and colleges, to enhance the effectiveness of teaching and learning processes [13].…”
Section: Discussionmentioning
confidence: 99%
“…QR codes offer advantages such as fast reading speed, error correction, multi-language support, and durability [11,22]. They have been utilized in various ways, including creating educational materials, conducting surveys and tests, expanding textbook content, and supporting the study of different subjects [12,13]. Research has demonstrated that the use of QR codes in the classroom can increase interest in learning, develop teamwork skills, and improve learning outcomes [23].…”
Section: Discussionmentioning
confidence: 99%
“…She stated that QR codeintegrated module can increase interest in learning. Meanwhile in the laboratory, QR code can be used in application for Laboratory Clearance Form (Rochmawati et al, 2018), for an inventory of science laboratory equipment (Mamin et al, 2017); to introduce chemical instruments to students (Nazar et al, 2022); and as practicum-teaching material (Rahmah et al, 2023). Based on the research that has been done, it can be seen that the QR code has a positive value in its use in the classroom and laboratory.…”
Section: Introductionmentioning
confidence: 99%